Recurrent melioidosis in patients in northeast Thailand is frequently due to reinfection rather than relapse. - Maharjan, B; Chantratita, N; Vesaratchavest, M; Cheng, A; Wuthiekanun, V; Chierakul, W; Chaowagul, W; Day, N; Peacock, S (2005)
Human melioidosis is associated with a high rate of recurrent disease, despite adequate antimicrobial treatment. Here, we define the rate of relapse versus the rate of reinfection in 116 patients with 123 episodes of recurrent melioidosis who were treated at Sappasithiprasong Hospital in Northeast Thailand between 1986 and 2005. Pulsed-field gel electrophoresis was performed on all isolates; isolates from primary and recurrent disease for a given patient different by one or more bands were examined by a sequence-based approach based on multilocus sequence typing. Overall, 92 episodes (75%) of recurrent disease were caused by the same strain (relapse) and 31 episodes (25%) were due to infection with a new strain (reinfection). The interval to recurrence differed between patients with relapse and reinfection; those with relapses had a median time to relapse of 228 days (range, 15 to 3,757 days; interquartile range [IQR], 99.5 to 608 days), while those with reinfection had a median time to reinfection of 823 days (range, 17 to 2,931 days; IQR, 453 to 1,211 days) (P = 0.0001). A total of 64 episodes (52%) occurred within 12 months of the primary infection. Relapse was responsible for 57 of 64 (89%) episodes of recurrent infection within the first year after primary disease, whereas relapse was responsible for 35 of 59 (59%) episodes after 1 year (P < 0.0001). Our data indicate that in this setting of endemicity, reinfection is responsible for one-quarter of recurrent cases. This finding has important implications for the clinical management of melioidosis patients and for antibiotic treatment studies that use recurrent disease as a marker for treatment failure.